Experimental and theoretical analyses of the flow phenomena in a fluidic flowmeter - Zheng, Zhensheng. (2008)
A target flowmeter for water measurements was designed and fabricated. The geometry of the flowmeter could be varied so that the study of each geometrical parameter on the flowmeter performance could be carried out independently.